Arithmetic Sequences: A, A + D, A + 2d, A + 3d, A + 4d
Arithmetic Sequences: A, A + D, A + 2d, A + 3d, A + 4d
A simple way to generate a sequence is to start with a number a, and add to it a fixed
constant d, over and over again. This type of sequence is called an arithmetic sequence.
The number a is the first term, and d is the common difference of the
sequence. The nth term of an arithmetic sequence is given by
an = a + (n – 1)d
The number d is called the common difference because any two consecutive terms of an
arithmetic sequence differ by d, and it is found by subtracting any pair of terms an and
an+1. That is
d = an+1 – an
(a) 2, 5, 8, 11, …
(b) 1, 2, 3, 5, 8, …
5–2=3
8–5=3
11 – 8 = 3
Step 2: Now, compare the differences. Since each pair of adjacent terms
has the same difference 3, the sequence is arithmetic and the
common difference d = 3 .
Solution (b):
2–1=1
3–2=1
5–3=2
8–5=3
An arithmetic sequence is determined completely by the first term a, and the common
difference d. Thus, if we know the first two terms of an arithmetic sequence, then we can
find the equation for the nth term.
Example 2: Find the nth term, the fifth term, and the 100th term, of the arithmetic
sequence determined by a = 2 and d = 3.
an = a + (n – 1)d.
So, to find the nth term, substitute the given values a = 2 and
d = 3 into the formula.
an = 2 + (n – 1)3
Step 2: Now, to find the fifth term, substitute n = 5 into the equation for
the nth term.
a5 = 2 + (5 – 1)3
= 14
Step 3: Finally, find the 100th term in the same way as the fifth term.
15 9 21
(b) t + 3, t + , t + , t + , ...
4 2 4
Solution (a): In order to find the nth and 100th terms, we will first have to
determine what a and d are. We will then use the formula for
finding the nth term.
a=4
d = 14 – 4
= 10
Step 2: Since we are given the fourth term, we can add the common
difference d = 10 to it to get the fifth term.
a5 = 34 + 10
= 44
Step 3: Now to find the nth term, substitute a = 4 and d = 10 into the
formula for the nth term.
an = 4 + (n – 1)10
Step 4: Finally, substitute n = 100 into the equation for the nth term to
get the 100th term.
Solution (b):
a=t+3
⎛ 15 ⎞
d = ⎜ t + ⎟ − ( t + 3)
⎝ 4⎠
15
= t + −t −3
4
15
= −3
4
3
=
2
Step 2: The fifth term is the fourth term plus the common difference.
Therefore,
⎛ 21 ⎞ 3
a5 = ⎜ t + ⎟ +
⎝ 4⎠ 2
24
=t+
4
=t+6
3
Step 3: Now, substitute a = t + 3, d = into the formula for the nth term.
2
3
an = ( t + 3) + ( n − 1)
2
Step 4: Finally, substitute n = 100 into the equation for the nth term that
we just found.
3
an = ( t + 3) + (100 − 1)
2
3
= t + 3 + ( 99 )
2
303
=t+
2
To find a formula for the sum, Sn, of the first n terms of an arithmetic sequence, we can
write out the terms as
S n = a + ( a + d ) + ( a + 2d ) + ... + ⎡⎣ a + ( n − 1) d ⎤⎦ .
S n = an + ( an − d ) + ( an − 2d ) + ... + ⎡⎣ an − ( n − 1) d ⎤⎦
Now, add the corresponding terms of these two expressions for Sn to get
Sn = a + ( a + d ) + ( a + 2d ) + ... + ⎡⎣ a + ( n − 1) d ⎤⎦
Sn = an + ( an − d ) + ( an − 2d ) + ... + ⎡⎣ an − ( n − 1) d ⎤⎦
2 Sn = ( a + an ) + ( a + an ) + ( a + an ) + ... + ( a + an )
The right hand side of this expression contains n terms, each equal to a + an, so
2 S n = n ( a + an )
n
Sn = ( a + an ) .
2
S n = a + ( a + d ) + ( a + 2d ) + ( a + 3d ) + ... + ⎡⎣ a + ( n − 1) d ⎤⎦
n
1. S n = ⎡ 2a + ( n − 1) d ⎤⎦
2⎣
⎛ a + an ⎞
2. S n = n ⎜ ⎟
⎝ 2 ⎠
∑ ki − c
i =1
represents the sum of the first n terms of an arithmetic sequence having the first term
a = k(1) + c = k + c and the nth term an = k(n) + c = kn + c. We can find this sum with
the second formula for Sn given above.
Example 4: Find the partial sum Sn of the arithmetic sequence that satisfies the given
conditions.
(a) a = 6, d = 3, and n = 7
14
(b) ∑ 2i − 7
i =1
Solution (a): To find the nth partial sum of an arithmetic sequence, we can use
either of the formulas
n ⎛ a + an ⎞
Sn = ⎡⎣ 2a + ( n − 1) d ⎤⎦ or S n = n ⎜ ⎟
2 ⎝ 2 ⎠
Step 1: To use the first formula for the nth partial sum, we only need to
substitute the given values a = 6, d = 3, and n = 7 into the
equation.
n
Sn = ⎡ 2a + ( n − 1) d ⎤⎦
2⎣
7
S7 = ⎡ 2 ( 6 ) + ( 7 − 1) 3⎤⎦
2⎣
7
= [12 + 18]
2
= 105
Solution (b): This is the sum of the first fourteen terms of the arithmetic
sequence having an = 2n – 7.
a=k +c
= 2 + (−7)
= −5
an = kn + c
a14 = 2(14) + (−7)
= 21
Step 2: Now that we know a = -5, n = 14, and a14 = 21, we can substitute
these values into the second formula for the nth partial sum to
find the fourteenth partial sum.
⎛ a + a14 ⎞
S14 = n ⎜ ⎟
⎝ 2 ⎠
⎛ −5 + 21 ⎞
= 14 ⎜ ⎟
⎝ 2 ⎠
= 112
Solution:
Step 1: First, we must find the values a, d, and n. Since the first even
number is zero, a = 0. The next even number is 2, so
d = 2 – 0 = 2. Since we are told to find the sum of the first 37
even numbers, n = 37.
a37 = 0 + ( 37 − 1) 2
= 18
⎛ 0 + 18 ⎞
S37 = 37 ⎜ ⎟
⎝ 2 ⎠
= 363
1 + 8 + 15 + … + 78
Solution:
a=1
d=8–1
=7
an = a + ( n − 1) d
78 = 1 + ( n − 1) 7
77 = ( n − 1) 7
11 = n − 1
12 = n
Step 2: Now that we know a = 1, n = 12, and a12 = 78 we can solve this
problem the same way as in example 4. Substitute the values for
a, d, and a12 into the formula for the nth partial sum.
⎛ 1 + 78 ⎞
S12 = 12 ⎜ ⎟
⎝ 2 ⎠
= 474